Treatment switching and associated economic outcomes in patients with plaque psoriasis treated with biologics: A retrospective analysis of German claims data 2016−2021 - Andreas Pinter; Ahmed M. Soliman; Karina C. Manz; Valeria Weber; Paul Ludwig; Anja Mocek; Ariane Höer; Mark G. Lebwohl (JEADV Clinical Practice)
Abstract Background Biologics are therapeutic options for the management of moderate−severe plaque psoriasis. Some patients need to switch biologic treatment to achieve satisfactory outcomes, which might have a considerable economic impact. Objectives We assessed the characteristics and switch rates of patients with plaque psoriasis initiating biologic treatment and compared healthcare resource utilization (HCRU) and associated costs for switching and non‐switching. Methods This study was a retrospective claims‐based analysis comprising a 182‐day baseline period to identify patient characteristics and a 365‐day follow‐up to assess switch rates, HCRU and associated costs. Data covering claims activity from 2016 to 2021 in a representative sample of four million individuals with statutory insurance in Germany was used. Results We identified 2565 patients with psoriasis initiating biologic treatment with anti‐IL‐17 (n = 1037), anti‐IL‐23 (n = 704), anti‐TNF‐α (n = 583) and anti‐IL‐12/23 (n = 241) agents. A total of 9.2% of patients switched therapy to another biologic during follow‐up, ranging from 4.9% (secukinumab) to 16.5% (etanercept). The probability of treatment switching was significantly lower in patients treated with risankizumab (p < 0.05) than in patients treated with other biologics except guselkumab (p = 0.14). HCRU and associated costs during the follow‐up were generally higher with a therapy switch (all‐cause: 32,263 ± 15,381€) than without (25,041 ± 12,090€). This applied to direct costs (outpatient services, hospitalization, drug treatment) and indirect costs (sickness benefits). Drug treatment accounted for the largest share of costs. Conclusions Treatment switching is frequent in patients with moderate−severe plaque psoriasis initiating biologic therapy and is associated with increased HCRU and associated costs. As the probability that a switch occurs within 365 days after treatment initiation widely differs between biologic agents, further research is warranted to determine the underlying reasons for switching to help establish clinically and economically sound therapy sequences.